Analisis Kebijakan Dalam Upaya Penegakan Hukum Lingkungan Hidup Di Indonesia - Baginda Parsaulian (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Forest fires are one of the environmental problems that often occur and are considered important so that they become local and global concerns. In Indonesia, forest and land fires (karhutla) continue to occur, especially in Sumatra, Riau and Kalimantan. Great forest and land fires have occurred in Riau and Kalimantan in 1997/1998 with severe impacts, including health problems, land accidents, aircraft crashes and smoke effects reaching neighboring countries. Law enforcement for environmental management is still difficult because of the difficulty in proving and determining the standard criteria for environmental damage Forest fires are one of the environmental problems that often occur and are considered important so that they become local and global concerns. In Indonesia, forest and land fires (karhutla) continue to occur, especially in Sumatra, Riau and Kalimantan. Great forest and land fires have occurred in Riau and Kalimantan in 1997/1998 with severe impacts, including health problems, land accidents, aircraft crashes and smoke effects reaching neighboring countries. Law enforcement for environmental management is still difficult because of the difficulty in proving and determining the standard criteria for environmental damage.